Fim de semana y Loteamiento clandestino: aproximaciones al universo popular de la vivienda en São Paulo (1970-1990) - Aravecchia-Botas, Nilce (2021)
This article is based on the analysis of two films by architect and urbanist Ermínia Maricato Fim de semana (1975) and Loteamento clandestino (1979) to reflect on some relations established in São Paulo, the largest South American metropolis, with the work by John Turner, Freedom to Build (published in 1977). It seeks to show the coincidences and departures between those who dedicated themselves to think social housing in Latin America, defending popular participation in its elaboration. Maricato, following the trail opened by other researchers at the University of São Paulo, elaborates an ethnographic approach to the outskirts of São Paulo, recording the construction of the house of the poor. This look reveals the impossibility of those subjects to access the formal housing market. In the late 1980s, the first municipal administration of the redemocratization period had Maricato as its housing secretary, and during her management, self-construction became state policy. It was a paradox: To support self-construction was to throw water into the windmill of precariousness or to defend libertarian ideas in the face of the oppression of the authoritarian state? Here we intend to discuss these issues, relating the Brazilian intellectual production with a more general movement, seeking to contribute to the debate.